Die altäthiopischen Personalpronomina der dritten Person Plural in der Funktion als Kopula - Weninger, Stefan (Aethiopica, 2014)
Gəʿəz (Classical Ethiopic) has two sets of personal pronouns in the plural. This paper offers a mainly statistical analysis that demonstrates that the two sets are free variants – however of rather different occurrence – without a recognizable functional differentiation.